THE ROLE OF EFFECTIVE COMMUNICATION SKILLS IN THE WORK READINESS EXPERIENCE OF PAP UNJ STUDENT - Revalina Novianti; Marsofiyati; Eka Dewi Utari (Adisam Publisher, 2025)
This study aims to analyze the role of effective communication skills in the work readiness experience of students in the Office Administration Education Study Program (PAP) of the State University of Jakarta (UNJ). Using a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and document analysis from final semester students and/or those with internship experience. The results of the study indicate that mastery of oral, written, active listening, and non-verbal communication significantly contributes to students' work readiness. Oral communication is crucial for professional interactions, while written communication is essential for the accuracy of administrative documents. Active listening and empathy skills support understanding instructions and building relationships. Furthermore, overall communication competency increases students' self-confidence and adaptability in the work environment. The implications of these findings emphasize the need for the UNJ PAP Study Program to strengthen the curriculum and learning practices that focus on developing holistic communication skills through real-world simulations and constructive feedback, in order to produce graduates who are not only technically competent but also resilient and adaptive.